(3GdeSFhdjI GdLfGFjI ddCTNGU GdeYfhjI aj bGfhf GdYbhHGJ GdGJMGOj dOhdI GdEeGQGJ GdYQHjI GdeJMOI (B: s (3OQGSI ebGQfI (B/ s - (3eMeO SYjO YHOGdQMefs; (3YeQ eMeO SGdes; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2014)
(3GdeSFhdjI GdLfGFjI ef COb GdOQGSGJ ai GdbGfhf GdLfGFi hEf GdLOd dGRGd eMJOekG ai Gdabg Mhd CSGS gPg GdeSFhdjI heOi EecGfjI JhGabgG eY GdeHGOiA GdbGfhfjI GdeSJbQI (B. (3hCjkG cGf GdCeQ abO GUHMJ gPg GdeSFhdjI MbjbI hGbYI hJYOOJ CMcGe GdbVGA ddbhd HgG ai GdJTQjYGJ GdJi CbQJgG (B: (3Hd hGLgJ HYV GdOhd GdJi CbQJgG Edi GdJhSY ajgG Ydi GdfMh GdPi aYdg GdeTQY GdaQfSi s
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdLfGFis
(3HHdjhLQGajG(B: (3UaMGJ (B285-294s
Keywords: (3GSGS GdeSFhdjI GdLfGFjI ddTNU GdeYfhis; (3GdGMcGe GdehVhYjI ddeSFhdjI GdLfGFjI ddGTNGU GdeYfhjIs; (3GdGTNGU GdeYfhjI GdeSFhdI LfGFjGs; (3TQhW bjGe GdeSFhdjI GdLfGFjI ddTNU GdeYfhis; (3GdLRGA GdeWHb Ydj GdGTNGU GdeYfhjIs; (3GdbhGYO GdGLQGFjI GdNGUI HGdeSFhdjI GdLfGFjI ddTNU GdeYfhis; (3GSe GdTNU GdeYfhj hMGdJgs; (3GdPeI GdeGdjI ddTNU GdeYfhis; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdLfGFjs